Konflik Sosial di Era Tata Kelola Demokratis: Kebijakan Kasus untuk Izin Lingkungan Limbah Berbahaya dan Beracun - Imam Nugraha; Nani Nurani Muksin (Pusat Riset dan Inovasi Nasional, 2025)
Globalization affects the fast-moving aspects of industrialization both at the central and regional levels, accompanied by the dynamics of the development process. Lakardowo Village is one of the villages in Mojokerto Regency, East Java Province. In this village there is a hazardous and toxic waste processing industry managed by PT.PRIA which was established based on the recommendation of the Mojokerto Regent Decree in 2017. The licensing for this environmental permit has had a negative impact, namely conflict between the Lakardowo village community and the company, the Mojokerto district government, and the pro-company community. In addition, another impact of this waste treatment activity is the source of water pollution and disease in the communities living in the factory area. This article attempts to analyze the chronological sequence and forms of conflict as well as the factors that cause conflict in Lakardowo village. The research method in this article is qualitative research. The findings in the field show that the conflict has occurred for many years and experienced various dynamics of conflict forms both horizontally and vertically.